2012
DOI: 10.1097/sap.0b013e318273f909
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Seeded on Acellular Dermal Matrix Grafts Enhance Wound Healing in a Murine Model of a Full-Thickness Defect

Abstract: Adipose-derived stem cells seeded on an ADM can enhance wound healing, promote angiogenesis, and contribute to newly formed vasculature, and VEGF-expressing ASCs can be detected after transplantation. This model could be used to improve the other clinical applications of ASCs and to decipher the detailed mechanism by which ASCs interact with wound tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 28 publications
4
89
0
1
Order By: Relevance
“…Aliquots of MSCs were characterized by their adhesiveness and fusiform shape. They were also characterized by flow cytometry for the surface markers CD45− and CD29+ and by differentiation [28].…”
Section: Isolation and Culture Of At-mscsmentioning
confidence: 99%
“…Aliquots of MSCs were characterized by their adhesiveness and fusiform shape. They were also characterized by flow cytometry for the surface markers CD45− and CD29+ and by differentiation [28].…”
Section: Isolation and Culture Of At-mscsmentioning
confidence: 99%
“…116,123 In one animal study, the use of ASCs seeded on an acellular dermal matrix found that it enhanced wound healing, promoted angiogenesis, and contributed to newly formed vasculature in murine mouse models. 124 Finally, MSC treatment of wounds reduces inflammation, accelerates wound healing, promotes granulation tissue, and increases angiogenesis. 2 MSC safety has been evaluated in a present metaanalysis and at this time appears to be safe for clinical use.…”
Section: Mscs: Mechanism(s) Of Actionmentioning
confidence: 99%
“…Successfully using MSCs for skin regeneration requires a sufficient quantity of MSCs and effective delivery of the MSCs to the wound site. Theoretically, ADM can serve as a scaffold for the delivery of MSCs to the target wound, while the MSCs promote retention and neovascularization of the scaffold [27].…”
Section: Discussionmentioning
confidence: 99%